2009
DOI: 10.1002/nme.2535
|View full text |Cite
|
Sign up to set email alerts
|

Limit analysis of plates using the EFG method and second‐order cone programming

Abstract: Published paperLe, Canh V., Gilbert, Matthew and Askes, Harm (2009) SUMMARYThe meshless Element-Free Galerkin (EFG) method is extended to allow computation of the limit load of plates. A kinematic formulation which involves approximating the displacement/velocity field using the moving least squares technique is developed. Only one displacement variable is required for each EFG node, ensuring that the total number of variables in the resulting optimization problem is kept to a minimum, with far fewer variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
3

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 41 publications
1
61
3
Order By: Relevance
“…Together with [15], this paper demonstrates that a numerical limit analysis procedure using a strain smoothing technique is capable of providing accurate solutions using a relatively small number of elements (nodes). It was also shown that most properties of CS-FEM found in elastic analysis, for instance superconvergent behavior, working well for extremely distorted elements and locking free behaviour (using one cell version), are retained here in plastic limit analysis.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Together with [15], this paper demonstrates that a numerical limit analysis procedure using a strain smoothing technique is capable of providing accurate solutions using a relatively small number of elements (nodes). It was also shown that most properties of CS-FEM found in elastic analysis, for instance superconvergent behavior, working well for extremely distorted elements and locking free behaviour (using one cell version), are retained here in plastic limit analysis.…”
Section: Discussionmentioning
confidence: 74%
“…It is known as the stabilized conforming nodal integration (SCNI) scheme. The SCNI scheme has been applied successfully to various problems, for instance, elastic analysis [12][13][14], plastic limit analysis [15], error estimation [16] and a stabilized mesh-free equilibrium model for limit analysis [17]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and locking problems can also be prevented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Le et al [9] proposed a numerical kinematic formulation using the Element-Free Galerkin (EFG) method and second-order cone programming (SOCP) to furnish good (approximate) upper-bound solutions for Kirchhoff plate problems governed by the von Mises failure criterion. It has also been demonstrated [9,10] that the EFG method is in general well suited for limit analysis problems, allowing accurate solutions to be obtained with relatively few nodes. Following this line of research, the main objective of this paper is to develop an equilibrium formulation which combines the EFG method with SOCP to obtain accurate solutions for both plate and slab problems.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of the scheme is that nodal values are determined by spatially averaging field values using the divergence theorem. The scheme has been applied successfully to various analysis problems [9,[12][13][14]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and the computational cost is much lower than when using Gauss integration.…”
Section: Introductionmentioning
confidence: 99%